Development of a Self-Evaluation Model Based on an Intelligent Tutoring System to Increase Student Learning Motivation in Basic Programming Subjects - Reskianissa, Anastasya; Wahyudin, Wahyudin; Fathimah, Nusuki Syari’ati (Universitas Pendidikan Indonesia, 2023)
Learning evaluation is a series of efforts to improve the quality of learning. Evaluation activities will have a good impact on students to encourage themselves in making improvements that affect their learning achievement. However, the implementation of learning evaluation in the field is not always easy. As the results of field studies conducted at SMK BPI Bandung, there are obstacles in the continuity of learning evaluations which the implementation has not been optimal. This study aims to develop a self-evaluation model based on an intelligent learning system (ITS) as a support in the learning process, where students can actively and independently evaluate their abilities, thereby increasing learning motivation which has an impact on their learning achievement. From the results of the research conducted using a nonequivalent pretest-posttest control group design, it was concluded that: 1) The evaluation media based on the ITS got a percentage value of 97.78% in the